The Impact of Affective Temperaments on Suicidal Ideation and Behaviors: Results from an Observational Multicentric Study on Patients with Mood Disorders - Mario Luciano; Gaia Sampogna; Bianca Della Rocca; Alessio Simonetti; Pasquale De Fazio; Marco Di Nicola; Giorgio Di Lorenzo; Maria Pepe; Fabio Sambataro; Maria Salvina Signorelli; Alexia Emilia Koukopoulos; Roberto Delle Chiaie; et al. (Brain Sciences, 2023)
Suicide ideation and behaviors are major health issues in the field of mental health. Several psychological and psychosocial factors have been taken into account as possible predictors of suicidality. Only recently affective temperaments have been considered as possible factors linked to suicide. This study aims to investigate the relationship between affective temperaments and suicidality, including the lifetime onset of suicide ideation, lifetime presence of suicide attempts and the total number of lifetime suicide attempts. This is a naturalistic multicentric observational study, involving outpatient units of seven University sites in Italy. Patients were administered with the short version of TEMPS-M and the Columbia Suicide Severity Rating Scale. A total of 653 participants were recruited, with a diagnosis of bipolar (55.7%), unipolar (35.8%) and cyclothymic disorder (8.4%). Regression models showed that the presence of lifetime suicide behaviors was increased in patients presenting trait related impulsivity (p < 0.0001), poor free-interval functioning (p < 0.05), higher number of affective episodes (p < 0.01), higher number of hospitalizations (p < 0.0001), cyclothymic and irritable affective temperaments (p < 0.05 and p < 0.05, respectively). Conversely, the presence of hyperthymic affective disposition reduced the likelihood of having suicidal behaviors (p < 0.01). Lifetime suicidal ideation was associated with trait-related impulsivity (p < 0.001), poor free-interval functioning (p < 0.05), higher number of affective episodes (p < 0.001) and of hospitalizations (p < 0.001). Depressive temperaments increased the likelihood of presenting suicidal ideation (p < 0.05), along with irritable temperaments (p < 0.01), contrary to hyperthymic affective (p < 0.05). Results of the present study confirm that affective disposition has a significant impact on the onset of suicidal ideation and behaviors, and that affective dispositions should be assessed in clinical settings to identify people at risk of suicide. Moreover, a wider clinical evaluation, including different clinical psychopathological dimensions, should be taken into consideration to develop effective preventive interventions.